2019
DOI: 10.29333/iji.2019.12160a
|View full text |Cite
|
Sign up to set email alerts
|

Developing and Validating a Scale to Measure Turkish and Kazakhstani ELT Pre-Service Teachers’ Intercultural Communicative Competence

Abstract: The purpose of this study is to describe the development of the Intercultural Communicative Competence Scale (ICCS). Two different groups from Turkey and Kazakhstan constituted the sample. The Turkish group (N=258) participated in the piloting process to develop the scale. The Kazakhstani group (N=314) was used to confirm the structure validity of the instrument. Based on review of literature, 76 items important for assessing ICC were generated. After expert revision for the face and content validity of the sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
19
2
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(24 citation statements)
references
References 14 publications
2
19
2
1
Order By: Relevance
“…In terms of CFA, no support was found for the original ICC scale. However, the present study result was consistent with the study done by several scholars,[ 9 13 16 30 ] showing a refined four-factor structure of ICC with very good fit indices. Furthermore, CFA indicates that the data fit the hypothesized model since the analysis confirmed that the model of this study has good construct validity (convergent and discriminant validity) as well as acceptable goodness of fit indices.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…In terms of CFA, no support was found for the original ICC scale. However, the present study result was consistent with the study done by several scholars,[ 9 13 16 30 ] showing a refined four-factor structure of ICC with very good fit indices. Furthermore, CFA indicates that the data fit the hypothesized model since the analysis confirmed that the model of this study has good construct validity (convergent and discriminant validity) as well as acceptable goodness of fit indices.…”
Section: Discussionsupporting
confidence: 93%
“…of items discrepancies in the present study conveyed in the literature are somewhat ascribed to individuals with different cultural backgrounds, translated language, sample heterogeneity, sample size, quality of data, and different statistical methods, for example, EFA vs. CFA employed. [ 9 13 16 30 33 ] Generally, the finding of the present study offers certain surplus support for[ 11 ] four-factor multidimensional intercultural competence scales and their possible generalizability to various eco-cultural contexts. Although the intercultural competence scale is one of the most comprehensive and widely used, it has never been translated into Amharic, and the research supporting its use in the Ethiopian context is insufficient.…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…Multicultural education is defined as the education incorporating various values from a variety of socio-cultural affiliations (Barzanò et al, 2017). When interacting in the midst of complex cultural differences, the teacher acts as an active facilitator in multicultural education to teach students intercultural competence (Kazykhankyzy & Alagözlü, 2019). Students can learn intercultural competence if they already have intercultural sensitivity.…”
Section: Introductionmentioning
confidence: 99%
“…The goodness of fit between the CFA-derived and hypothetical models may vary depending on the sample size [48]. The consulted literature indicates that a sample of 500 people is considered very good [54]. Therefore, the adequate goodness of fit presented by the instrument after applying the TFA can be interpreted based on the size of the study sample, which is 521 students.…”
Section: Discussionmentioning
confidence: 99%